Midregional Proadrenomedullin (MRproADM) Serum Levels in Critically Ill Patients Are Associated with Short-Term and Overall Mortality during a Two-Year Follow-Up. (7th August 2020) - Buendgens, Lukas; Yagmur, Eray; Ginsberg, Axel; Weiskirchen, Ralf; Wirtz, Theresa; Jhaisha, Samira Abu; Eisert, Albrecht; Luedde, Tom; Trautwein, Christian; Tacke, Frank; Koch, Alexander
Abstract : Adrenomedullin (ADM) is a peptide with pleiotropic effects in systemic inflammation. Its more stable precursor protein midregional proadrenomedullin (MRproADM) can be measured more reliably compared to ADM. Our objective was to investigate the potential role of MRproADM as a diagnostic and prognostic biomarker in critically ill patients at the intensive care unit (ICU). We therefore measured MRproADM in 203 ICU patients and 66 healthy controls. We found that MRproADM levels are significantly increased in critically ill patients as compared to healthy controls. MRproADM levels are significantly increased in patients with sepsis, but its diagnostic value for identifying sepsis is numerically lower than that of established markers (e.g., interleukin-6, C-reactive protein, and procalcitonin). MRproADM levels are closely correlated to endothelial and organ dysfunction, inflammation, and established clinical scores (APACHE II, SOFA, and SAPS2). MRproADM concentrations correlate with vasopressor use but not fluid balance. Increased MRproADM levels (cut − off > 1.4 nmol / L ) in critically ill patients are independent predictors of ICU and overall mortality during a follow-up of up to 26 months (OR 3.15 for ICU mortality, 95% CI 1.08-9.20, p = 0.036 ; OR for overall mortality 2.4, 95% CI 1.12-5.34, p = 0.026 ). Our study demonstrates the potential of MRproADM serum levels as a prognostic biomarker in critical illness for ICU mortality and long-term survival during follow-up.